Determinants of global palm oil demand: a gravity approach - Rini Yayuk Priyati (Economic Journal of Emerging Markets, 2018)
This paper reviews the determinants of global palm oil trade using the gravity model. This model helps to explain how the shift in demand for palm oil has affected trade flows among trading partners. We decompose the effects of growth in the regional markets, location, and the reduction in the palm oil price relative to other edible oils, on palm oil exports. We find that standard variables suggested by the gravity literature, such as the growth of GDP, GDP per capita, and location, are indeed important determinants of palm oil trade. Given the preceding results, we simulate whether the economic growth of Indonesia’s trading partners can explain the growth in palm oil export demand from Indonesia. The simulation results for top ten Indonesia’s trading partners suggest that the growth of palm oil imports is a great deal higher than the growth of income for all countries.